The RoboCOS Study: Development of an international core outcome set for the comprehensive evaluation of patient, surgeon, organisational and population level impacts of robotic assisted surgery. - Clare Robertson; Shafaque Shaikh; Jemma Hudson; Patrick Garfjeld Roberts; David Beard; Terry Mackie; Cameron Matthew; Craig Ramsay; Katie Gillies; Marion Campbell (PLoS ONE)
Background The introduction of robot-assisted surgery is costly and requires whole system transformation, which makes the assessment of benefits (or drawbacks) complex. To date, there has been little agreement on which outcomes should be used in this regard. The aim of the RoboCOS study was to develop a core outcome set for the evaluation of robot-assisted surgery that would account for its impact on the whole system. Methods Identification of a long-list of potentially relevant outcomes through systematic review of trials and health technology assessments; interviews with individuals from a range of stakeholder groups (surgeons, service managers, policy makers and evaluators) and a focus group with patients and public; prioritisation of outcomes via a 2-round online international Delphi survey; consensus meeting. Results 721 outcomes were extracted from the systematic reviews, interviews and focus group which were conceptualised into 83 different outcome domains across four distinct levels (patient, surgeon, organisation and population) for inclusion in the international Delphi prioritisation survey (128 completed both rounds). The consensus meeting led to the agreement of a 10-item core outcome set including outcomes at: patient level (treatment effectiveness; overall quality of life; disease-specific quality of life; complications (including mortality); surgeon level (precision/accuracy; visualisation); organisation (equipment failure; standardisation of operative quality; cost-effectiveness); and population (equity of access). Conclusion The RoboCOS core outcome set, which includes the outcomes of importance to all stakeholders, is recommended for use in all future evaluations of robot-assisted surgery to ensure relevant and comparable reporting of outcomes.